2020
DOI: 10.3390/su12041288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Classification of Mobile Financial Services Sustainability Using Structural Equation Modeling and Multiple Criteria Decision-Making Methods

Abstract: Despite the fast emergent of smartphones in day-to-day activity, the sustainable development of mobile financial services (MFS) remains low partially due to online consumer’s trust and perceived risk. This research broadens the trust and the perceived risk at the multi-dimensional for understanding and prioritizing alternatives of MFS decision. A combined methodology; structural equation modeling (SEM) with two multiple criteria decision-making (MCDM) methods such as a technique for order of preference by simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 181 publications
(220 reference statements)
0
31
0
2
Order By: Relevance
“…Perceived risk refers to the risk that users believe they may have when certain accounting platforms do not guarantee the security of their data or transactions. In other words, perceived risk negatively influences attitudes [40,41] and the intention to use information technology [42] or remote payment systems [43,44]. In our research, risks were considered essential because they are considered a precedent for users' intention to use information technologies.…”
Section: Perceived Risk (Pr)mentioning
confidence: 83%
“…Perceived risk refers to the risk that users believe they may have when certain accounting platforms do not guarantee the security of their data or transactions. In other words, perceived risk negatively influences attitudes [40,41] and the intention to use information technology [42] or remote payment systems [43,44]. In our research, risks were considered essential because they are considered a precedent for users' intention to use information technologies.…”
Section: Perceived Risk (Pr)mentioning
confidence: 83%
“…Past studies found that trust significantly impacts consumer behaviour (intention and adoption) in uncertain environments (To & Trinh, 2021). Furthermore, Gbongli et al (2020) confirmed that customer's trust positively impacts customer's intention to use electronic banking.…”
Section: Mobile Perceived Trustmentioning
confidence: 62%
“…In literature, scholars have paid close attention to the methodology mentioned above due to its ability to handle complex situations. Supplier selection [61], material selection [62], personnel selection [63], technology selection [64], performance measurement [65], and financial decision making [66] are a few examples of MCDM applications. The decision about the problem described above is based on a set of factors, sub-factors, and alternatives.…”
Section: Methodsmentioning
confidence: 99%
“…Following the sensitivity analyses, a comparison with the existing literature was performed. Although a few studies [7,45,65,102] addressed the selection of m-banking technologies, none of them addressed human judgement of uncertainty when making a decision. The proposed fuzzy model, which employs fuzzy-BWM and fuzzy-TOPSIS to select m-banking applications, is unique in that it takes into account human uncertainty when selecting m-banking applications.…”
Section: Comparative Analysismentioning
confidence: 99%